Dilemas de vida e de morte: um estudo sociojur??dico sobre a ortotan??sia - Almeida, Jane de Oliveira Rabelo de (2017)
The objective of this study is to verify that the main issues may involve the social acceptance of the right to the implementation of ortotanasia in the context of the transformations brought about by the evolution of technology, Bioethics and, consequently, Law. It is a current theme, complex in itself, therefore involving the view of diverse disciplines, such as Biology, Philosophy and Sociology, which are represented in their constituent elements, such as common sense, science and culture, respectively. Religion stands out in this context, because the subject has the object of death and the treatment given to it. Theoretically, it was tried to characterize the evolution of the law in front of the social development resulting from the technological transformations and the emergence of Bioethics; analyzing ortotanasia in the context of the unfolding of the terminality of life; highlighting cultural aspects that can mobilize popular acceptance of controversial issues in general and ortotanasia in particular (common sense, science); to raise, among law students, objective and subjective aspects that may justify the non-undertaking of the artificial prolongation of life in terminal patients by the physician. Empirically, the results showed that there is still a lot of ignorance on the subject, which hinders or prevents answers that clearly point out the main difficulties of the social acceptance of ortotanasia. However, the tendency to recognize the right to refuse to therapeutic obstinacy was clear, which in itself already represents an advance against traditional culture.